Building the event or Modernity in the novel "Naguib Mahfouz's novels as a model" (Czech Journal of Multidisciplinary Innovations, 2024)
Naguib Mahfouz's novels are distinguished by their inclusion of many narrative styles that are not familiar in the classical novel, and the structure of the novel event is one of the most important of these styles, if not the most important of them at all, in addition to the narrative paradoxes at the level of time, place and characters. This study dealt with the description and analysis of the structure of the event in Naguib Mahfouz's novels, and the study showed the definition of the event linguistically and technically, and the importance of the event in the Arab novel as a pillar of the novel, and the methods of constructing the event within the novel, and these methods include: the traditional method, the modern method, and then constructing the event in Naguib Mahfouz's novels, and these novels are: Miramar, The Harafish novel, The Dome's Joys novel, The New Cairo novel, The Nile Chatter novel, The Thief and the Dogs novel, and Midaq Alley novel.